2019
DOI: 10.1057/s41300-019-00061-x
|View full text |Cite
|
Sign up to set email alerts
|

Young driver enforcement within graduated driver licensing systems: a scoping review

Abstract: Young drivers have the highest crash rates when compared with other groups of drivers. One countermeasure that has successfully reduced these crash rates is graduated driver licensing. However, young drivers' compliance with graduated driver licensing requirements decreases as they gain driving experience. This paper systematically reviews the literature in order to identify how enforcement practices can be used to influence the compliance of young drivers within graduated driver licensing systems. The review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 89 publications
0
12
0
Order By: Relevance
“…A. Bates, Matthews, Simpson, & Bates, 2016;L. Bates, Rodwell, & Matthews, 2019;Jones, Simpson, Briggs, & Dorsett, 2016).…”
Section: Methods Review Methodologymentioning
confidence: 99%
“…A. Bates, Matthews, Simpson, & Bates, 2016;L. Bates, Rodwell, & Matthews, 2019;Jones, Simpson, Briggs, & Dorsett, 2016).…”
Section: Methods Review Methodologymentioning
confidence: 99%
“…Evaluation studies suggest that the Queensland GDL, which was improved in 2007 [27], was effective at reducing young driver crashes, fatalities, and serious injuries [28]. Research indicates that parental engagement in GDL programs, especially parental regulation of young people's driving, rather than that of police or other regulatory agencies, is important for the success of GDL programs [29,30].…”
Section: Contextmentioning
confidence: 99%
“…Over the long term, private vehicle ownership is positively correlated with road traffic accidents, and a short-term increase in private vehicle ownership inevitably leads to a rise in fatalities. To avoid the rise in fatalities caused by increased private vehicle ownership, approaches like increasing the difficulty in obtaining drivers' licenses or setting up classified drivers' licenses can be implemented in order to increase drivers' proficiency and avoid high accident rates caused by novice drivers [49]. Additionally, studies have shown that risky driving behaviors such as the frequent use of mobile phones also increase the fatality rate of non-professional drivers [50].…”
Section: Private Vehicle Ownership and Road Traffic Safetymentioning
confidence: 99%